Successful Treatment of Fetal Intraperitoneal Administration of Immunoglobulin in a Case of Fetal Hemolytic Anemia with 131,072-Fold Anti-E Alloimmunization - Masashi Yoshida; Hideo Matsuda; Eijiro Hayata; Akio Watanabe; Miho Oeda; Kenichi Furuya (Hindawi Limited, 2011)
Object. We present here the case of severe fetal anemia caused by anti-E antibody positive, which showed a favorable course only with fetal intraperitoneal administration of immunoglobulin. Case. The mother was 31 years old, blood type B Rh : CCDee, gravida 1, with no history of transfusion. Anti-E antibody was detected in the maternal cross-match test at the 18th gestational week. In percutaneous umbilical blood sampling, the umbilical blood hemoglobin level was 9.1 g/dL and the result of the direct Coombs' test was positive at the 26th gestational week. Immunoglobulin injection into fetal abdominal cavity (IFAC) was administered a total 7 times. During the pregnancy, the indirect Coombs' test showed a 131,072-fold increase. Conclusion. In this case, IFAC to block the reticuloendothelial system Fc receptor was successful. This procedure is promising as one of the treatment options for blood group incompatible pregnancy.